Transparency and Accountability Model for Education Costs at MI Manba'ul Huda - Ara Hidayat; Asri Sulastri; Femi Sri Wahyuni (al-Afkar, Journal For Islamic Studies, 2025)
Effective financial management can support the quality of education. Well-managed finances are those that implement transparency and accountability. This is crucial because financing is a crucial factor and influences educational activities. This research is a field study using descriptive qualitative methods to explain the transparency and accountability model at MI Manba'ul Huda in Bandung City. Data collection was conducted through interviews, observation, and documentation. The results of this study indicate that the transparency and accountability model has been implemented at the madrasah, but challenges remain in managing educational costs.